Does local adaptation cause high population differentiation of Silene Latifolia Y chromosomes? - Muir, Graham (Evolution, 2011)
Natural selection can reduce the effective population size of the nonrecombining Y chromosome, whereas local adaptation of Y-linked genes can increase the population divergence and overall intra-species polymorphism of Y-linked sequences. The plant Silene latifolia evolved a Y chromosome relatively recently, and most known X-linked genes have functional Y homologues, making the species interesting for comparisons of X- and Y-linked diversity and subdivision. Y-linked genes show higher population differentiation, compared to X-linked genes, and this might be maintained by local adaptation in Y-linked genes (or low sequence diversity). Here we attempt to test between these causes by investigating DNA polymorphism and population differentiation using a larger set of Y-linked and X-linked S. latifolia genes (than used previously), and show that net sequence divergence for Y-linked sequences (measured by Da, also known as δ) is low, and not consistently higher than X-linked genes. This does not support local adaptation, instead, the higher values of differentiation measures for the Y-linked genes probably result largely from reduced total variation on the Y chromosome, which in turn reflect deterministic processes lowering effective population sizes of evolving Y-chromosomes.